The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.21897/rmvz.922
|View full text |Cite
|
Sign up to set email alerts
|

Lesión en la carne y adicción de nutrientes en el ayuno antes del sacrificio de cerdos

Abstract: Objetivo. Se realizaron dos experimentos en un beneficiadero en Brasil, dirigido a la evaluación de las lesiones en la piel de cerdo y la canal en la área de espera del beneficiadero y destinado a evaluar los efectos de glucosa (G), bicarbonato de sodio (SB) y vitamina E (VE) añadida al agua durante el ayuno antes de la masacre en el rendimiento de la canal, de órganos y la calidad de la carne. Materiales y métodos. En primer ensayo incluyó a 1.000 cerdos, observados en la zona de descanso del beneficiadero ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The effects of waiting time before loading and pen space allowance on carcass lesions have already been discussed. This association seems to confirm the hypothesis that longer waiting and wider lairage pens may have caused more fights among the pigs within each batch, as lesions on the neck and head are typically caused by fights and aggressions between pigs [55]. Concerning the effect of the trailer identified in the present study, several authors have already investigated the effects of vehicle design on pig welfare and carcass lesions [1,27,38,65].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The effects of waiting time before loading and pen space allowance on carcass lesions have already been discussed. This association seems to confirm the hypothesis that longer waiting and wider lairage pens may have caused more fights among the pigs within each batch, as lesions on the neck and head are typically caused by fights and aggressions between pigs [55]. Concerning the effect of the trailer identified in the present study, several authors have already investigated the effects of vehicle design on pig welfare and carcass lesions [1,27,38,65].…”
Section: Discussionsupporting
confidence: 87%
“…In those pigs, higher transport densities and thus less space allowance per animal were associated with decreased prevalence of low-quality pork. Petrolli et al [55] indicated an association between the presence of larger stalls and a higher prevalence of carcass injuries, suggesting, however, that this is linked to the fact that larger stalls favor the mixing of unfamiliar animals, coming from different pens or farms. The presence of admixture between unfamiliar animals increases the possibility of hierarchical fights among pigs, increasing carcass injuries [1,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation